2019
DOI: 10.1155/2019/5304524
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 25-Gauge Vitrectomy for Tractional and Nontractional Diabetic Macular Edema with Proliferative Diabetic Retinopathy

Abstract: The benefit of pars plana vitrectomy with internal limiting membrane peeling for tractional macular edema and diffuse nontractional macular edema in diabetic retinopathy has been reported. Although these studies had included various stages, use of conventional 20-gauge vitrectomy system, small number of cases, single-center study, and lack of retinal structure measurements were limitations. We compared one-year outcomes of 25-gauge vitrectomy for refractory diabetic macular edema with or without the tractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…The effect of internal limiting membrane (ILM) peeling on DME has also been investigated, and it has been found that this can result in a lower rate of recurrence following surgery [12]. The incidence of additional therapy following surgery has been reported as 6-20% in studies with a shorter follow-up [13,14]. Bonnin et al [15] found an incidence of 30% in their longer follow-up study.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of internal limiting membrane (ILM) peeling on DME has also been investigated, and it has been found that this can result in a lower rate of recurrence following surgery [12]. The incidence of additional therapy following surgery has been reported as 6-20% in studies with a shorter follow-up [13,14]. Bonnin et al [15] found an incidence of 30% in their longer follow-up study.…”
Section: Introductionmentioning
confidence: 99%
“…As the availability of more user-friendly microsurgical instruments and high incision speed devices increases, there is a tendency for surgical intervention to diabetic retinopathy and DME in earlier stage. PPV surgery is thought to have positive effects on DME therapy by reducing VEGF concentration in the eye and increasing oxygenation or nutrient diffusion of the retina (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Vitrectomy for the treatment of DME was first performed in 1992, 24 and many studies have been done since. [25][26][27][28][29] All of FIG. 1.…”
Section: Discussionmentioning
confidence: 99%